Cost Efficiency Affects Sustainable Operations - Chen, Chun-Ying; Chen, Chun-Hung; Hsu, Ai-Chi (International Journal of Economics and Financial Issues, 2018)
This study adopted a cost efficiency model to assess the operational efficiency of the banking industry in Taiwan. Empirical results show that the Bank of Taiwan, Taiwan Cooperative Bank, and First Commercial Bank have higher operational efficiency than the other banks. Banks with relatively low operational efficiency include Taipei Star Bank, the Enterprise Bank of Hualien, which was merged into the CTBC Bank, and the ABN AMRO-acquired Taitung Business Bank, which together with ABN AMRO’s other business in Taiwan, was later acquired by the Australia and New Zealand Banking Group (ANZ) and renamed ANZ Bank (Taiwan). These findings show that banks with low operational efficiency are unable to maintain sustainable operations. Keywords: Operational efficiency, cost efficiency, data envelopment analysis JEL Classifications: C1, G1, J3